Pap Smear Images Classification Using Machine Learning:A Literature Matrix - Shahrina Binti Ismail; Nur Ain Alias; Wan Azani Mustafa; Mohd Aminudin Jamlos; Hiam Alquran; Hafizul Fahri Hanaf; Khairul Shakir Ab Rahman (MDPI, 2024)
Indexed by WOS/ Scopus